Managing financial institutions - Gardner, Mona J. (Thomson / South-Western, 2005)
This dynamic text allows learners to analyze and apply theory to managing performance for financial institutions. It is up-to-date, including new types of financial institutions and the evolving nature of the financial services industry. Not only does this text include risk management of financial institutions, it includes managing and analyzing different types of financial institutions. Additionally, this text provides the necessary institutional detail that learners need to know to be successful in the management of financial services firms. Numerous applied cases are included so learners can better understand how the concepts are applied. Targeted at the MBA corporate finance course, this book can also be used for both a banking course and financial institution management course.